Political Education for Novice Voters to Increase Voter Participation in the Simultaneous Elections of 2024 - Sri Musrifah; Hasanul Bulqiyah; Denny Fahrian; Sumarno Sumarno; Lilik Indah Yuliyanti; Sri Ulandari; Bagus Ade Wijaya; Heru Setyawan; Egita Manda Putri Juliansa (Universitas Lambung Mangkurat, 2024)
Students in grade XI high school who are novice voters participated in the Community Service Program to address the following issues: (a) first-time voters who are still unsure about their voting responsibilities and the purpose of elections; (b) low voter participation rates in the 2020 Tuban district elections; (c) limited socialization to novice voters in preparation for the simultaneous elections in 2024; and (d) unstable novice voters, particularly those who are high school students, who still require political introduction and education. This Community Service activity aims to increase the voter participation rate of novice voters in Tuban district in the simultaneous elections of 2024. The Community Service activity uses the Participatory Action Research (PAR) method, which includes education, coaching, and awareness-raising for novice voters conducted through direct presentations and Q&A sessions with grade XI students at SMAN 1 Grabagan and MAN 1 Tuban. The result of this Community Service activity is an increase in the participation rate of novice voters in Tuban district in the simultaneous elections of 2024.